2022
DOI: 10.3390/electronics11203330
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity Threats, Countermeasures and Mitigation Techniques on the IoT: Future Research Directions

Abstract: The Internet of Things (IoT) interconnects physical and virtual objects embedded with sensors, software, and other technologies, which exchange data using the Internet. This technology allows billions of devices and people to communicate, share data, and personalize services to make our lives easier. Despite the multiple benefits offered by IoT, it may also represent a critical issue due its lack of information security. Since the number of IoT devices has been rapidly increasing all over the world, they have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 64 publications
(101 reference statements)
0
23
0
Order By: Relevance
“…This paper builds upon our previous study about the threats to IoT, in which we found that DoS attacks pose the most threat to IoT networks and that detection techniques are required to address this challenge [ 9 ].…”
Section: Introductionmentioning
confidence: 94%
“…This paper builds upon our previous study about the threats to IoT, in which we found that DoS attacks pose the most threat to IoT networks and that detection techniques are required to address this challenge [ 9 ].…”
Section: Introductionmentioning
confidence: 94%
“…al. [8] study that looks at the dangers and threats to devices connected to the internet, like smartwatches, home security systems, and smart fridges. This systematic review examines different ways to understand and manage these risks to keep our devices and information safe.…”
Section: Related Workmentioning
confidence: 99%
“…This prevents legitimate users from accessing the services or resources they need. Attackers may use various techniques, including SYN flood attacks, where a surge of SYN requests is sent without completing the handshake with ACK responses, or ICMP flooding, which overwhelms the target with ping requests [62], [63]. By exploiting vulnerabilities inherent in the way TCP/IP protocols operate, DoS attacks can cause significant disruptions, making the mitigation and prevention of such attacks a critical concern for network administrators and security professionals.…”
Section: Figure 3 Dos Attackmentioning
confidence: 99%